2011
DOI: 10.5232/ricyde2011.02501
|View full text |Cite
|
Sign up to set email alerts
|

Clima motivacional percibido, necesidades psicológicas y motivación intrínseca como predictores del compromiso deportivo en adolescentes. (Perceived motivational climate, psychological needs and intrinsic motivation as predictors of sport commitment in adolescent athletes).

Abstract: Clima motivacional percibido, necesidades psicológicas y motivación Clima motivacional percibido, necesidades psicológicas y motivación intrínseca como predictores del compromiso deportivo en adolescentes intrínseca como predictores del compromiso deportivo en adolescentes El estudio analizó la predicción del clima motivacional percibido, la satisfacción de las necesidades psicológicas básicas y la motivación intrínseca sobre la adherencia a la práctica deportiva. Se utilizó una muestra de 580 deportistas con … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
30

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 34 publications
2
17
1
30
Order By: Relevance
“…Almagro, Sáenz-López, González-Cutre, and Moreno-Murcia (2011), studied the prediction of the motivational climate in athletes, the basic psychological needs, and the intrinsic motivation related to sports practice adherence. A sample of 580 athletes with an average age of 14.5 answered questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Almagro, Sáenz-López, González-Cutre, and Moreno-Murcia (2011), studied the prediction of the motivational climate in athletes, the basic psychological needs, and the intrinsic motivation related to sports practice adherence. A sample of 580 athletes with an average age of 14.5 answered questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was a significant increase in the athletes' levels of social relations, autonomy and perceived competence only in the experimental group. Almagro et al 27 found that task-involving motivational climates positively predicted highschool athletes' basic psychological needs (autonomy, competence and relatedness). Similarly Boyce et al 26 found that perceptions of a task-involving climate positively predicted perceived competence in a group of student-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The satisfaction of these basic psychological needs depends on several sociocontextual factors: cooperation, the availability of autonomous election of tasks and behaviours 23 and the learning climate structured by the instructor 24 . Cooperative learning should satisfy the need of relatedness since it has been linked to augmented relationship among peers 25 , a task orientation climate should enhance the perceived competence levels of the subjects 26 , and the openness of election (being able to choose, to have a saying on what is happening in the training session) should definitely make an impact on the individuals' autonomy 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Son varios los análisis que determinan correspondencia entre la motivación y actividad física (Conde y Almagro, 2013;Owen, Astell-Burt y Lonsdale, 2013;Spittle y Byrne, 2009). Más concretamente, Almagro, Sáenz-López, González-Cutre y Moreno-Murcia (2011) y Carriedo, González y López (2013 estudian el clima motivacional dentro del área de Educación Física, dando consignas generales sobre la concreción de un clima motivacional adecuado basado en la motivación intrínseca (Méndez-Giménez, Cecchini, Fernández-Río y . En relación, el Clima Tarea se corresponde con una buena actitud del alumno hacía la asignatura y el deseo de realizar tareas desafiantes, caracterizandose por satisfacer las necesidades de los discentes, la superación personal y la cooperación; reconociendo el esfuerzo sobre los resultados como meta de éxito (Cervelló, Moreno, Martínez, Ferriz y Moya, 2011;Gutiérrez y col., 2011;Moreno y Hellín, 2007), originando actitudes favorables hacia el ejercicio (Galván y col., 2011).…”
Section: Introductionunclassified